Performance Analysis of Interaction between Smart Glasses and Smart Objects Using Image-Based Object Identification - Jacek Rumiński; Adam Bujnowski; Tomasz Kocejko; Jerzy Wtorek; Alexey Andrushevich; Martin Biallas; Rolf Kistler (International Journal of Distributed Sensor Networks)
We propose the use of smart glasses to collaborate with smart objects in the Internet of Things environment. Particularly we are focusing on new interaction methods and the analysis of acceptable reaction times in the process of object recognition using smart glasses. We evaluated the proposed method using user studies and experiments with three different smart glasses: Google Glass, Epson Moverio, and the developed eGlasses platform. We conclude that using the proposed method it is possible to recognize objects and process information allowing object detection below the average acceptance response times specified by almost all participants in the user study. Additionally, we showed that eye-tracking can be used for simple interaction between a user and a graphical user interface presented in the near-to-eye display.